Multifunctional Agriculture Meets Health Care: Applying the Multi‐Level Transition Sciences Perspective to Care Farming in the Netherlands. Issue 2 (26th October 2012) - Hassink, Jan; Grin, John; Hulsink, Wim
Abstract Care farming is a promising example of multifunctional agriculture: it is an innovation at the crossroads of the agricultural and healthcare sectors. Our objective is to develop a framework for understanding the success of initiatives in this field. We link empirical data with the multi‐level perspective from the transition sciences and extend this perspective with insights from the literature on entrepreneurship, alliance management and organisational attributes. This framework allows us to explain the success of the three major types of initiatives: (1) individual care farms; (2) regional foundations of care farmers; and (3) care institutions collaborating with groups of farmers at a regional level. We propose that the main factors responsible for the success of initiatives are the commitment and competences of the entrepreneur, the creation of alliances, the quality of the new regional organisations and the implementation of the care farm services in care organisations. The relative importance of the factors varies between the different types of initiatives and local and regional levels.